Prevalence of metabolic syndrome in non-diabetic, pregnant Angolan women according to four diagnostic criteria and its effects on adverse perinatal outcomes - Dos Prazeres Tavares, Hamilton [UNESP]; Dos Santos, Débora Cristina Damasceno Meirelles [UNESP]; Abbade, Joelcio Francisco [UNESP]; Negrato, Carlos Antonio [UNESP]; De Campos, Paulo Adão; Calderon, Iracema Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Springer Nature, 2016)
Background: Metabolic syndrome (MetS) is a cluster of risk factors for type 2 diabetes (Type2 DM) and cardiovascular diseases (CVD), and its prevalence varies based on region, population, and sex. Newborns of women with MetS have a greater risk of adverse perinatal outcomes. This study explores the prevalence of metabolic syndrome in non-diabetic, pregnant Angolan women and the adverse perinatal outcomes associated with it. Methods: This cross-sectional study collected the demographic, anthropometric and clinical data of 675 pregnant women in the maternity ward of General Hospital in Huambo, Angola. Metabolic syndrome was defined using four criteria: the third report of the National Cholesterol Education Program Adult Treatment Panel (ATPIII), the Joint Interim Statement (JIS), and definitions by both Bartha et al. and Chatzi et al. Results: The crude prevalence of metabolic syndrome was 36.6 % based on the JIS definition, 29.2 % based on NCEP ATPIII, 12.6 % based on Chatzi et al. and 1.8 % based on Bartha et al. In general, the prevalence of adverse perinatal outcomes was 14.1 %. Conclusions: There was a high prevalence of metabolic syndrome, depending on the criteria used, and thus a great need to harmonize the criteria and cutoff points. Perinatal adverse outcomes were higher in pregnant women with metabolic syndrome.
Keywords: Angola; Metabolic syndrome; Pregnancy perinatal outcome; Prevalence